PENGARUH PENAMBAHAN ABU TANKOS SAWIT DAN ABU AMPAS TEBU PADA TANAH LEMPUNG EKSPANSIF TERHADAP PEMADATAN TANAH - Siagian, Nur Kholidiah (Jurnal Teknik Sipil : Rancang Bangun, 2024)
In Aceh Tamiang Regency, Aceh province, various soil characteristics are observed. Expansive clay soil in Bukit Sabun Hamlet, Bandung Jaya Village, Manyak Payed District, Aceh Tamiang Regency, exhibits poor quality, leading to concerns such as cracks, subsidence, and shifting in buildings constructed on this land. The research aims to assess alterations in the physical and mechanical properties of expansive clay soil after incorporating palm oil tankos ash and sugarcane bagasse ash. The analysis is conducted according to the AASHTO (American Association of State Highway and Transportation) classification system. Test results indicate a decrease in water content during the Atterberg limit test. For instance, the Liquid Limit (LL) value of the original soil at 55.55% decreases to 54.89% when mixed with 25% bagasse ash and palm oil ash. Similarly, the Plasticity Index (PI) value reduces from 33.05% to 13.23% after mixing with the same ash combination. Standard proctor testing reveals that the 25% ash mixture yields optimal soil compaction results, indicating a potential breakthrough in enhancing soil stability.